2014
DOI: 10.1371/journal.pone.0100965
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Daytime Sleepiness and Cognitive Performance Testing in Patients with Primary Insomnia

Abstract: ObjectiveWhile individuals with insomnia consistently complain of cognitive impairment, previous studies on the effect of insomnia on objective measures of cognitive function have obtained ambiguous results. The relationship between daytime sleepiness and cognitive manifestations in insomnia patients is not clear.MethodsThirty-six primary insomnia patients (PIPs) and 26 good sleep controls (GSCs) with age and gender matched manner were included in the study. Participants underwent an overnight polysomnography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
4
25
2
2
Order By: Relevance
“…Thirteen studies reported a neuropsychological measure of inhibitory control as an outcome (Crenshaw and Edinger, 1999; Edinger et al, 2000, 2008; Szelenberger and Niemcewicz, 2001; Backhaus et al, 2006; Sagaspe et al, 2007; Haimov et al, 2008; Covassin et al, 2011; Joo et al, 2013; Siversten et al, 2013; Fortier-Brochu and Morin, 2014; Liu et al, 2014; Perrier et al, 2015). Three of these measured inhibitory control through the continuous performance test (Crenshaw and Edinger, 1999; Edinger et al, 2000, 2008) and one through the continuous performance test II (Fortier-Brochu and Morin, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported a neuropsychological measure of inhibitory control as an outcome (Crenshaw and Edinger, 1999; Edinger et al, 2000, 2008; Szelenberger and Niemcewicz, 2001; Backhaus et al, 2006; Sagaspe et al, 2007; Haimov et al, 2008; Covassin et al, 2011; Joo et al, 2013; Siversten et al, 2013; Fortier-Brochu and Morin, 2014; Liu et al, 2014; Perrier et al, 2015). Three of these measured inhibitory control through the continuous performance test (Crenshaw and Edinger, 1999; Edinger et al, 2000, 2008) and one through the continuous performance test II (Fortier-Brochu and Morin, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Driver numbness causes changes in facial and eye features, and many techniques and algorithms have been developed to recognize facial features that detect numbness. Lopar and Ribaric demonstrated the speed and precision of the Violla-Jones algorithm as a tool for monitoring facial features (9). These studies used image processing based on the Violla-Jones algorithm to identify facial features, detect driver fatigue, and determine the level of driver warning.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia with short sleep duration negatively affects neurocognitive performance, especially sustained attention [51,52] and increases daytime sleepiness [50,53]. Furthermore, insomniacs with short sleep and daytime sleepiness have slowed reaction times [54], and all of the above contribute to ANMAS. Not all insomniacs have short sleep duration.…”
Section: Anmas and Sleep Habitsmentioning
confidence: 99%